Design of a 25 W Picohydro Power Plant Using Proportional Integral Derivative (PID) - Slamet Hariadi, Slamet Hariadi; Yunior, Yudhis Thiro Kabul (Utan Kayu Publishing, 2025)
Energy is a very important resource in achieving social, economic and environmental goals for sustainable development and is a supporter of national economic activities. Energy use in Indonesia is increasing rapidly in line with economic growth and population growth. Two-thirds of the total national energy needs come from commercial energy and the rest comes from biomass which is used traditionally (non-commercially).Pikohydro is a hydroelectric power plant that has a power of under 5kW per unit. Picohydro usually has three main components, namely water (energy source), turbine and generator. Picohydro can be used as an alternative to oil-fueled diesel power plants which are not environmentally friendly and have relatively expensive operational costs. This system is designed by utilizing the flow of water flowing in the river using the on grid method because the current in the river tends to be stable if you don't use batteries because it is more economical. Apart from that the voltage is relatively unstable because the voltage that is converted to AC electricity tends to fluctuate, therefore To increase the voltage, use a DC to DC converter which is equipped with a PID system to stabilize the voltage. In this DC to DC converter, it is used to provide a DC output voltage that varies in size according to the demand on the load.